Parenting styles and dimensions in parents of children with developmental disabilities. Issue 5 (12th September 2022) - Marston, Emma; Cho, Chi C.; Pridham, Karen; McPherson, Amy C.; Polfuss, Michele
Abstract: Parenting influences child development. There is limited research, however, related to parenting children who have developmental disabilities. The aims of this study were to: (1) describe the parenting styles and dimensions of parents of children with developmental disabilities and (2) assess differences in parenting styles and dimensions among parents of children with autism spectrum disorder (ASD), Down syndrome (DS), and spina bifida (SB). Secondary data analysis was conducted from a nationwide cross‐sectional study of 496 parents of children aged 5–16 years with ASD ( n  = 180), DS ( n  = 156), or SB ( n  = 160). Parent scores indicated high use of the authoritative parenting style and associated parenting dimensions, mid‐to‐low use of the permissive parenting style, and low use of the authoritarian parenting style and associated dimensions. Variation in parenting styles and dimensions among parents was primarily related to the child's diagnosis and family income. An unanticipated but positive finding was that parents with lower family incomes had significantly higher scores for the authoritative parenting style. Results from this study can inform future research that might inform clinical practice.